2023
DOI: 10.3389/fnut.2023.1066789
|View full text |Cite
|
Sign up to set email alerts
|

Propolis polyphenols: A review on the composition and anti-obesity mechanism of different types of propolis polyphenols

Abstract: Obesity, one of the most common nutritional diseases worldwide, can lead to dyslipidemia, high blood sugar, high blood pressure, and inflammation. Some drugs have been developed to ameliorate obesity. However, these drugs may cause serious side effects. Therefore, there is an urgent need for alternative “natural” remedies including propolis. Studies have found that propolis has excellent anti-obesity activity in in vitro and in vivo models during the past decades, of which polyphenols are the key component in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 102 publications
(98 reference statements)
2
8
0
Order By: Relevance
“…In an osteoarthritis rat model, a study highlighted the positive impact of quercetin treatment on mitigating intestinal flora disorder and restoring fecal metabolite abnormalities [ 166 ]. Multiple studies have been undertaken to investigate the influence of propolis and its key constituents on gut microbiota in both health and disease settings [ 53 , 85 , 97 , 98 , 154 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 ]. Although early research suggests that propolis may help optimize gut health, more comprehensive studies are needed before clinical recommendations can be made.…”
Section: Gut Microbiotamentioning
confidence: 99%
“…In an osteoarthritis rat model, a study highlighted the positive impact of quercetin treatment on mitigating intestinal flora disorder and restoring fecal metabolite abnormalities [ 166 ]. Multiple studies have been undertaken to investigate the influence of propolis and its key constituents on gut microbiota in both health and disease settings [ 53 , 85 , 97 , 98 , 154 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 ]. Although early research suggests that propolis may help optimize gut health, more comprehensive studies are needed before clinical recommendations can be made.…”
Section: Gut Microbiotamentioning
confidence: 99%
“…Various research has demonstrated that phenolic components such as catechin, quercetin, and chlorogenic acid have been associated to energy expenditure and lower body mass index (BMI) [ 18 – 22 ]. Polyphenols may have a role in body weight management by activating-oxidation, inducing satiety, increasing energy expenditure, promoting adipocyte death, and stimulating lipolysis [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Propolis was reported to contain 10 % volatile compounds, 50–55 % resins (flavonoids, phenolic acids and, their esters), 30–40 % beeswax, 5–10 % pollens, and other substances [3] . The plant source dictates the chemical makeup of propolis, which is influenced by various factors like season, climate, bee species, and collection techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Propolis was used by the Egyptians, Greeks, and Romans for its general medicinal properties as well as for the treatment of specific skin ailments [3] . Propolis has long been known for its ability to reduce inflammation and treat wounds and ulcers [2,3] . Its pharmaceutical application is still used today in treatments and personal care products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation